Lipopolysaccharidelike immunological properties of cell wall glycoproteins isolated from Cytophaga johnsonae. - de Jong, D M (1991)
Glycoproteins (GP) previously shown to be involved in the gliding motility of Cytophaga johnsonae were examined for biological activities characteristic of lipopolysaccharide (LPS). These integral membrane proteins activated 70Z/3 pre-B cells to synthesize immunoglobulin M, induced B cells to synthesize non-antigen-specific polyclonal immunoglobulin, induced macrophages to produce tumor necrosis factor, and modulated the antibody response to type III pneumococcal polysaccharide in the absence of thymus-derived (T) lymphocytes. Except for the GP activity in the 70Z/3 assay, all activities of the GP were comparable to or greater than those of LPS. No LPS was detected in the preparations of GP used or in the phenol-water extracts of C. johnsonae. The mechanism by which these GP exerted their biological activities was distinct from that of LPS, since LPS-resistant C3H/HeJ mice responded to GP. Furthermore, biologically inactive diphosphoryl lipid A obtained from nontoxic LPS of Rhodopseudomonas sphaeroides (an analog of toxic lipid A), which is an antagonist of LPS, did not block the induction of tumor necrosis factor by GP in macrophages. These results showed that the cell surface GP from C. johnsonae are potent LPS-like activators of B cells and macrophages. We suggest that these GP might be good candidates for use in developing an effective adjuvant system.